Compassionate communalism : welfare and sectarianism in Lebanon - Cammett, Melani Claire, 1969- (Cornell University Press, 2014)
In Lebanon, religious parties such as Hezbollah play a critical role in providing health care, food, poverty relief, and other social welfare services alongside or in the absence of government efforts. Some parties distribute goods and services broadly, even to members of other parties or other faiths, while others allocate services more narrowly to their own base. In Compassionate Communalism, Melani Cammett analyzes the political logics of sectarianism through the lens of social welfare. On the basis of years of research into the varying welfare distribution strategies of Christian, Shia Muslim, and Sunni Muslim political parties in Lebanon, Cammett shows how and why sectarian groups deploy welfare benefits for such varied goals as attracting marginal voters, solidifying intraconfessional support, mobilizing mass support, and supporting militia fighters. Cammett then extends her arguments with novel evidence from the Sadrist movement in post-Saddam Iraq and the Bharatiya Janata Party in contemporary India, other places where religious and ethnic organizations provide welfare as part of their efforts to build political support. Nonstate welfare performs a critical function in the absence of capable state institutions, Cammett finds, but it comes at a price: creating or deepening social divisions, sustaining rival visions of the polity, or introducing new levels of social inequality.Compassionate Communalism is informed by Cammett's use of many methods of data collection and analysis, including Geographic Information Systems (GIS) analysis of the location of hospitals and of religious communities; a large national survey of Lebanese citizens regarding access to social welfare; standardized open-ended interviews with representatives from political parties, religious charities, NGOs, and government ministries, as well as local academics and journalists; large-scale proxy interviewing of welfare beneficiaries conducted by trained Lebanese graduate students matched with coreligionist respondents; archival research; and field visits to schools, hospitals, clinics, and other social assistance programs as well as political party offices throughout the country.